Strategi Pembelajaran Efektif Bagi Siswa Slow Learner: Sebuah Kajian Literatur - Baiq Yuni Wahyuningsih; Ni Made Yeni Suranti (Indonesian Journal of Elementary and Childhood Education, 2023)
Slow learner students experience many delays in the learning process because slow learners are a condition where children experience slow learning, skill, slowness in receiving information and slowness in capturing the teacher's explanations during the learning process. This research aims to determine the learning strategies of slow learner students in elementary schools by using a literature review method, namely by reading various journals and other publications related to research topics by collecting and taking core points from previous research. There were 15 articles used in this research obtained from Google Scholar. Based on the results of research conducted using the literature review method, learning strategies for slow learner students in elementary schools can be carried out by providing assistance or services to students in the form of; teaching method accommodation services, assignment and research accommodation services, time demands, learning environment and motivation for students to increase their interest in learning. So it can be concluded that learning strategies for slow learner students include; 1). Teacher strategies in classroom management with specifications and qualifications for changes in students' behavior and personality. 2). The teacher's strategy in treating slow learner students in regular classes is by placing slow learner students in the front row, rotating them by paying attention to the students' condition 3). Teacher strategy in giving assignments to slow learner students 4). Teacher strategies in motivating slow learner students.